(untitled) (Fiep Bulletin - online, 2014)
The Judo is a sport commonly starts in childhood and often accompanies the person throughout maturational period. The aim of this study is to analyze the development of strength in judo male residents in the western city of Rio de Janeiro, aged 10-15 years. Therefore, we performed a cross-sectional and descriptive ex post facto that assessed the body mass index (BMI) and the strength of lower limbs (LL), upper (UL) and abdomen (ABD) 64 judo male at least six months of practice, divided into two groups: Pre-puberty (PP), 10-12 years, and pubescent (PU), from 13 to 15 years. In BMI was observed a significant increase between phases as well as a sharp gain strength in the upper limbs, followed by a gain less significant in ABD and a loss of strength in lower limbs. The gain in strength between phases PP and PU are real and derive the increase in muscle mass and improves anaerobic lactic capacity. However, the decrease in strength of the lower limbs found in the study is inversely related to the increase in BMI, because the gain in muscle mass and strength athletes in this sport are considerably larger in the upper limbs. Thus, we can diagnose in the present study the specific characteristics of judo athletes in the transition period between phases PP and PU.